Genome-wide association study identifies a common variant associated with risk of endometrial cancer - Spurdle, Amanda B.; Thompson, Deborah J.; Ahmed, Shahana; Ferguson, Kaltin; Healey, Catherine S.; O'Mara, Tracy; Walker, Logan C.; Montgomery, Stephen B.; Dermitzakis, Emmanouil T.; Fahey, Paul; Montgomery, Grant W.; Webb, Penelope M.; et al. (Nature Genetics, 2011)
Endometrial cancer is the most common malignancy of the female genital tract in developed countries. To identify genetic variants associated with endometrial cancer risk, we performed a genome-wide association study involving 1,265 individuals with endometrial cancer (cases) from Australia and the UK and 5,190 controls from the Wellcome Trust Case Control Consortium. We compared genotype frequencies in cases and controls for 519,655 SNPs. Forty seven SNPs that showed evidence of association with endometrial cancer in stage 1 were genotyped in 3,957 additional cases and 6,886 controls. We identified an endometrial cancer susceptibility locus close to HNF1B at 17q12 (rs4430796, P = 7.1 × 10-10) that is also associated with risk of prostate cancer and is inversely associated with risk of type 2 diabetes. © 2011 Nature America, Inc. All rights reserved.
CRIS-Team Scopus Importer:2021-07-19